2021
DOI: 10.1186/s10194-021-01274-y
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in resting state functional connectivity in pediatric migraine

Abstract: Background Migraine affects roughly 10% of youth aged 5–15 years, however the underlying mechanisms of migraine in youth are poorly understood. Multiple structural and functional alterations have been shown in the brains of adult migraine sufferers. This study aims to investigate the effects of migraine on resting-state functional connectivity during the period of transition from childhood to adolescence, a critical period of brain development and the time when rates of pediatric chronic pain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Previous studies showed that pharmacological prophylaxis has little or no efficacy in the pediatric population of patients with migraine [15][16][17], and that future research should identify non-pharmacological approaches [17]. Addressing migraine early in this population is of importance in consideration of the fact that brain alterations begin early in youth with migraine, as showed in neuroimaging studies [44,45]. The result of our openlabel trial supports the hypothesis that a combined approach that includes patient education and mindfulness-based programs can be very useful in populations of adolescents [20] and represent a valid alternative to pharmacological prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that pharmacological prophylaxis has little or no efficacy in the pediatric population of patients with migraine [15][16][17], and that future research should identify non-pharmacological approaches [17]. Addressing migraine early in this population is of importance in consideration of the fact that brain alterations begin early in youth with migraine, as showed in neuroimaging studies [44,45]. The result of our openlabel trial supports the hypothesis that a combined approach that includes patient education and mindfulness-based programs can be very useful in populations of adolescents [20] and represent a valid alternative to pharmacological prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that the relationship between pain perception, pain modulation, and emotion regulation in the fibromyalgia may be related to weakened connections between different networks in the brain, including VIN, AUN, and DMN [37,38]. Prolonged pain had altered functional connectivity between VIN and DMN, and this alteration had become more pronounced with an increase in the pain cycle and age [39]. Clinical pain severity in patients with fibromyalgia were associated with a reduction in connectivity between the tectum and primary visual and auditory cortex.…”
Section: Discussionmentioning
confidence: 97%
“…While the DAN-RIFG connectivity did not differ from zero in both concussed adolescents with and without such a history, there was a trend toward a negative association between these regions in concussed adolescents with a history of migraines. Prior resting state studies demonstrated that adolescents who experience migraines have significantly altered patterns of connectivity when compared to controls as well as younger children [38] and adults [39] suffering from migraines. Importantly, functional connectivity in adolescents with migraines is dependent on age and time between the last migraine attack and scan [38].…”
Section: Discussionmentioning
confidence: 99%
“…Prior resting state studies demonstrated that adolescents who experience migraines have significantly altered patterns of connectivity when compared to controls as well as younger children [38] and adults [39] suffering from migraines. Importantly, functional connectivity in adolescents with migraines is dependent on age and time between the last migraine attack and scan [38]. Considering that symptoms of a migraine may overlap with those experienced during the earlier stages of concussion (e.g., headaches, dizziness, fogginess, nausea), this find-ing might indicate that adolescents with migraines are more vulnerable to DAN-RIFG connectivity disruption due to concussion than adolescents without premorbid migraines.…”
Section: Discussionmentioning
confidence: 99%